SIMPLE CARBON AND ORGANIC MATTER ADDITION IN ACID SULFATE SOILS AND TIME-DEPENDENT CHANGES IN PH AND REDOX UNDER VARYING MOISTURE REGIMES - Michael, Patrick (Asian Journal of Agriculture, 2020)
Abstract. Michael PS. 2020. Simple carbon and organic matter addition in acid sulfate soils and time-dependent changes in pH and redox under varying moisture regimes. Asian J Agric 4: 23-29. It has been shown recently that addition of dead plant materials as organic matter in acid sulfate soils (ASS) creates microenvironments conducive for soil microbes to reduce the sulfate content and redox potential (Eh), thereby increasing the pH of sulfuric soil and sustaining the pH of sulfidic soil, respectively. The time course of effects of addition of organic matter however was not clearly established. This was study conducted to assess the time course of effect of soil carbon and organic matter following addition of glucose and acetate as carbon and lucerne hay as organic matter source, respectively. The conditions of the treatments were either anaerobic (flooded) or aerobic (under 75% field capacity). The results showed that the effects of addition of amendments on pH and Eh of ASS are immediate but treatment dependent. Organic matter as a multiple food sources for soil microbe was more effective in reducing the soil and increasing the pH of the sulfuric and the sulfidic soil, respectively. The effects of acetate were comparatively higher than glucose, dependent on the type of microbial ecology that was engaged by these resources being simple carbon sources. The overall increase in pH and reduction in Eh was immediate within the first three days but the changes in the soil properties measured were reversed over time. The reversal in the mechanism inducing the changes in pH and Eh ceased as the microbial metabolic resources used as metabolic substrate to generate alkalinity got depleted.